2015
DOI: 10.1089/cbr.2014.1805
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccines: Can They Improve Survival?

Abstract: In patients with metastatic cancer, therapeutic anticancer vaccines are rarely associated with objective antitumor responses; so, many investigators have focused on progression-free survival (PFS) as a key endpoint for clinical trials. However, it is not clear that PFS is a surrogate for overall survival (OS), and OS may be a more appropriate endpoint because of the effects on long-term memory in the adaptive immune system. Recently, reported vaccine trials were reviewed to determine their primary and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The results in each arm of this randomized trial are quite similar to results previously reported for single arm trials of TCV [ 20 ], and DCV [ 21 ]. The lack of correlation between PFS and OS was also observed in the earlier trials, and has been observed for other immunotherapies that may provide long-lasting immune benefit [ 27 ]. Examples of FDA-approved agents that improved OS but had unimpressive ORR or PFS include sipuleucel-T in prostate cancer, [ 28 ] and ipilimumab in melanoma [ 29 ].…”
Section: Discussionmentioning
confidence: 63%
“…The results in each arm of this randomized trial are quite similar to results previously reported for single arm trials of TCV [ 20 ], and DCV [ 21 ]. The lack of correlation between PFS and OS was also observed in the earlier trials, and has been observed for other immunotherapies that may provide long-lasting immune benefit [ 27 ]. Examples of FDA-approved agents that improved OS but had unimpressive ORR or PFS include sipuleucel-T in prostate cancer, [ 28 ] and ipilimumab in melanoma [ 29 ].…”
Section: Discussionmentioning
confidence: 63%
“…Previously, other vaccines and immunomodulatory antibodies have not shown improvement in PFS: sipuleucel-T and PROSTVAC-VF in prostate cancer and ipilimumab and eltrapuldencel-T in melanoma were associated with no improvement in PFS and response rate, but statistically significant benefit in OS (29). The incidence of activating EGFR and ALK translocations was not evaluated in the trial, as the TKIs targeting the referred mutations were not accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these disappointing clinical results may relate to the products themselves, and especially the TAA being presented, but we also know that the immune system of each patient and the biology of each patient's cancer are important determinants of whether induced or enhanced immune responses can result in clinical benefit. However, several immunotherapy products have been associated with improved overall survival despite lack of a high objective response rate and or a significant impact on progression-free survival [103]. Further clinical investigation of DC vaccines is warranted.…”
Section: Resultsmentioning
confidence: 99%